Extra Articular Supracondylar Femur Fractures Managed with Locked Distal Femoral Plate or Supracondylar Nailing: A Comparative Outcome Study - Gill, SPS (J Clin Diagn Res, 2017)
INTRODUCTION: Despite recent evolution in the operating techniques and surgical implants, debate continues around the choice of implant for management of distal femur fractures. High rates of complications and union difficulties continues to make them a momentous therapeutic challenge. AIM: To compare the outcome of locked compressive plating versus retrograde nailing in the management of extra articular supracondylar femur fractures. MATERIALS AND METHODS: In this randomized prospective study, 42 patients with extra-articular distal femur fractures were segregated into two groups based on internal fixation with distal femoral locking plate (n=22) and retrograde nail (n=20). Clinical and radiological parameters were studied and functional evaluation was done at 18 months with KSS score. RESULTS: A significant difference in terms of mean duration of surgery and intraoperative blood loss was discerned in favour of plating group although complication rates were equivalent between the groups. Mean duration until union was 26.5 weeks (SD=12.9; range 12 to 64 weeks) in the locked plating and 22.6 weeks (SD=13.1: range 12 to 60 weeks) in the retrograde nail group. The difference came out to be statistically insignificant. Fractures in nailed patients united earlier but the difference was not statistically significant with similar overall union rates. Functional scores too were comparable between them. We deduce that surgical planning and expertise rather than the choice of implant are more crucial for optimal results. CONCLUSION: Nailing proved more cumbersome intraoperatively due to escalated operating time and blood loss and successive anterior knee pain necessitating implant removal but this detriment may be offset by an inclination towards earlier union. With Less Invasive Stabilization System (LISS), technical errors are more common and less forgiving and must be overcome with proper preoperative planning and intraoperative attention to detail.